The Elastin Receptor Complex: A Unique Matricellular Receptor with High Anti-tumoral Potential - Scandolera, Amandine; Odoul, Ludivine; Salesse, Stéphanie; Guillot, Alexandre; Blaise, Sébastien; Kawecki, Charlotte; Maurice, Pascal; El Btaouri, Hassan; Romier-Crouzet, Béatrice; Martiny, Laurent; Debelle, Laurent; Duca, Laurent (Frontiers in Pharmacology, 2016)
Elastin, one of the longest-lived proteins, confers elasticity to tissues with high mechanical constraints. During aging or pathophysiological conditions such as cancer progression, this insoluble polymer of tropoelastin undergoes an important degradation leading to the release of bioactive elastin-derived peptides (EDP), named elastokines. EDP exhibit several biological functions able to drive tumor development by regulating cell proliferation, invasion, survival, angiogenesis, and matrix metalloproteinase expression in various tumor and stromal cells. Although several receptors have been suggested to bind elastokines (αvβ3 and αvβ5 integrins, galectin-3), their main receptor remains the Elastin Receptor Complex (ERC). This heterotrimer comprises a peripheral subunit, named Elastin Binding Protein (EBP), associated to the Protective Protein/Cathepsin A (PPCA). The latter is bound to a membrane-associated protein called Neuraminidase-1 (Neu-1). The pro-tumoral effects of elastokines have been linked to their binding onto EBP. Additionally, Neu-1 sialidase activity is essential for their signal transduction. Consistently, EDP-EBP interaction and Neu-1 activity emerge as original anti-tumoral targets. Interestingly, besides its direct involvement in cancer progression, the ERC also regulates diabetes outcome and thrombosis, an important risk factor for cancer development and a vascular process highly increased in patients suffering from cancer. In this review, we will describe ERC and elastokines involvement in cancer development suggesting that this unique receptor would be a promising therapeutic target. We will also discuss the pharmacological concepts aiming at blocking its pro-tumoral activities. Finally, its emerging role in cancer-associated complications and pathologies such as diabetes and thrombotic events will be also considered.